Performance evaluation of flexural and shear behaviours of lightweight geopolymer concrete / Iftekhair Ibnul Bashar - Iftekhair , Ibnul Bashar (2022)
Enunciation of the embryonic materials from industrial by-products is vital to address the ever-depleting virgin construction materials. The Fly ash (FA), palm oil clinker (POC), and manufactured sand (M-sand) are three industrial by-products from the coal operated power plants, palm oil industries, and quarry industries. These industrial by-products are available in abundance in Southeast Asia. Their regular generation as by-product from the high demandable main products - electricity, palm oil, and granite, are unavoidable and certain. So, these industrial by-products can ensure sustainability of production and supply on demand. FA is a well-known pozzolan. The chemical properties of FA collected from a type of coal operated power plant, are about consistent, and the particles are round and fine. These two specialities of FA have made it preferable more than other industrial pozzolanic by-product powders such as palm oil fuel ash, and rice husk ash. POC is lightweight, porous, and pozzolan; hence it is considered as a potential lightweight aggregate that could be used in geopolymer concrete. A concrete made of FA, POC, and M-sand is environment friendly; and implementation of that concrete in real construction will benefit to environment, and economical growth. It is imperative to exemplify the mechanical behaviour, material interaction properties (bond resistance, shear stress), and structural behaviour of a new material before using it in the structural application. This research project presented the failure mechanism of POC-based GC (P-GC) and granite-based GC (G-GC) under compression, bond properties, and structural behaviour through flexural, and shear test of reinforced concrete beams. The compression toughness and energy absorption at elastic and plastic states due to the influence of POC at micro-level crack propagation were investigated. The pull-out load and slip response of a rebar embedded in P-GC and G-GC, was shown the role of aggregate in influencing the bond-slip responses. Further, Flexural and shear behaviour of reinforced concrete beams made of P-GC and G-GC were investigated and the experimental results were compared with the analysed results using partial interaction concept. The moment-curvatures of P-GC and G-GC beams were calculated from the compression load-deformation and rebar pull-out-slip results to comprehend the feasibility of P-GC in structural application. The results show that the ultimate moment of resistances of both beams were comparable for the concretes of similar grade. The elastic limit of P-GC was lower than G-GC, hence, and the first crack initiated in P-GC earlier compared to G-GC. The midspan-deflections varied due to the difference of stiffnesses of P-GC and G-GC. The outcome of the whole project is beneficial for the engineers to adopt POC as sustainable construction material.